Geographical distribution patterns of Carcharocles megalodon over time reveal clues about extinction mechanisms. (30th March 2016) - Pimiento, Catalina; MacFadden, Bruce J.; Clements, Christopher F.; Varela, Sara; Jaramillo, Carlos; Velez‐Juarbe, Jorge; Silliman, Brian R.
Abstract: Aim: Given its catastrophic consequences, the extinction of apex predators has long been of interest to modern ecology. Despite major declines, no present‐day species of marine apex predator has yet become extinct. Because of their vulnerability, understanding the mechanisms leading to their extinction in the past could provide insight into the natural factors that interact with human threats to drive their loss. We studied the geographical distribution patterns of the extinct macro‐predatory shark Carcharocles megalodon in order to elucidate its pathway to extinction. Location: World‐wide from the Miocene to the Pliocene ( c.  23–2.6 Ma). Methods: A meta‐analysis of C. megalodon occurrence records was performed using the Paleobiology Database as a platform. The data were binned into geological time slices, and the circular home range around each data point was mapped in reconstructions made in GPlates. We then quantitatively assessed the species' geographical range and global abundance over time, and the relationship between distribution and climate. Results: The pathway to extinction of C. megalodon probably started in the late Miocene with a decrease in its global abundance. This decrease was then followed by a decline in its geographical range during the Pliocene. Although the extinction of C. megalodon has been attributed to climate change, we found no evidence of direct effects of global temperature. Instead, we found that the collapse in geographical distribution coincided mainly with a drop in the diversity of filter‐feeding whales and the appearance of new competitors (large predatory whales and the great white shark). Main conclusions: This research represents the first study of the distributional trends of an extinct, cosmopolitan apex predator in deep‐time. Our results suggest that biotic factors, and not direct temperature limitations, were probably the primary drivers of the extinction of the largest marine apex predators that ever lived.